2013
DOI: 10.3346/jkms.2013.28.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Usefulness of Eosinopenia in the Pediatric Intensive Care Unit

Abstract: Eosinopenia, a biomarker for infection, has recently been shown to be a predictor of adult mortality in the intensive care unit (ICU). Our study assessed the usefulness of eosinopenia as a mortality and an infection biomarker in the pediatric ICU (PICU). We compared the PICU mortality scores, eosinophil count and percentage at ICU admission between children who survived and those who did not survive and between children with infection and those without infection. A total of 150 patients were evaluated. The ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 24 publications
(41 reference statements)
1
21
4
1
Order By: Relevance
“…We did not find an association between eosinophil count at ICU admission and hospital mortality, this contrast with that reported by other authors [10, 12, 30]. The retrospective design of our study, including an unselected population of critically ill patients and increased frequency of sepsis in the group of non-survivors, could explain this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not find an association between eosinophil count at ICU admission and hospital mortality, this contrast with that reported by other authors [10, 12, 30]. The retrospective design of our study, including an unselected population of critically ill patients and increased frequency of sepsis in the group of non-survivors, could explain this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study found no significant difference in the eosinophil count and percentage in children with and without infection in the pediatric ICU. (19) As seen above, the most important difference from literature is our work done in ill-appearing children in emergency department. Therefore, the comparing of our results with the literature is not easy.…”
Section: The Upper Limit Of Eosinophils In Blood Is 350 Cells/mm 3 (1contrasting
confidence: 38%
“…(18,19) We found that a low blood eosinophil count (≤ 50 cells/mm 3 ) is similar to a high CRP level (≥1.22 mg/dL) and a high neutrophil count (>5100 cells/mm 3 ) for predicting bacterial infection in the pediatric emergency department. However, none of them had sufficient discriminatory power.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, hemogram parameters which are inexpensive laboratory tests can be helpful for diagnosis of sepsis. Although WBC C was indicated as a sepsis criteria in the last guideline, some studies have demonstrated that it has low sensitivity and specificity for sepsis diagnosis [ 8 , 9 ]. Neutrophil count (Neu C ) and eosinophil count (Eo C ) were used as a predictor of sepsis in the early 1990s [ 9 13 ].…”
Section: Introductionmentioning
confidence: 99%